School based cardiopulmonary resuscitation and automated external defibrillation program - Mohd Ariffin, Ikamaya; Mohd. Said, Nurumal (IIUM Press, International Islamic University Malaysia, 2017)
This book is describing the management of type 2 diabetes in Malaysia. A marked increase of type 2 diabetes and associated morbidity and mortality rate over the last 10 years has been recorded in Malaysia. Ineffective diabetes management and a lack of self-care practice among type 2 diabetic patients have been identified as the major reasons for this problem. Research in other countries has highlighted a range of factors influencing effective self-care of type 2 diabetes including patients’ perspectives of diabetes, sociocultural issues, religious beliefs and support from healthcare. This book will provide information on how the patients with type 2 diabetes are currently being supported within the primary and secondary healthcare settings in urban areas in Malaysia in enhancing their self-care practice. It also provide information on how healthcare professionals who involved in the diabetes management perceived their roles and support that they gave to the patients. This book is intended to increase understanding of the healthcare professionals on the issues around the diabetes management and self-care support for patients with type 2 diabetes.This book is derived from a research project title “An exploration of self-care practice and self-care support of patients with type 2 diabetes in Malaysia”. However, the content of this book will focusing on the review of the current evidence of self-care support for patients with type 2 diabetes, the information on how this research was conducted, the findings derived from the data that is consist of the interview of the patients with type 2 diabetes, interviews with the healthcare professionals involved in the management of diabetes in the primary and secondary healthcare settings, observation of the diabetes consultation session between the patients and healthcare professionals and the analysis of the selected documents that are currently used in guiding the management of type 2 diabetes within the Malaysian healthcare settings.It is hope that this book will shed the light on the issues around the self-care support provision of type 2 diabetes particularly in Malaysia. Within the data that is presented in this book it is clear that, the increased incidence of uncontrolled type 2 diabetes is not merely due to poor self-care practice by patients, but also due to constraints in service delivery and underdevelopment of self-care support provision. The evidence generated can assist in the development of strategies to improve the quality of care and facilitate changes in the self-care support provision in Malaysia.